Improving the Slippage Resistance of Successors of the Mars Instrument “Heat Flow Property Package Instrument” (HP3) Using Bekker’s Spaced-Linked Track - Siebo Reershemius (International Journal of Aerospace Engineering)
The “Heat Flow Property Package Instrument” (HP3) is part of NASA’s current Mars mission “InSight”, which was launched in 2018 and currently operates on the surface of Mars. The instrument needs to remain at its initial position and orientation during operation. Although the landing site can have significant tilt and can be covered with low cohesion soil, any mechanical excitation might make the instrument slip. Therefore, the instrument is using a tailored feet design, which can withstand lateral loads. Future instruments might require higher resistance against slip. This can be due to stronger tilted landing sites or due to higher shocks emitted from stronger penetration probes. This paper introduces a novel design for those instruments based on the idea of the “spaced-link track” of Bekker to further minimize slippage. This design concept is originally used on tracks of heavy machinery. It is presented how the major design feature can be incorporated into the current design. A newly developed analytical-numerical model is utilized to estimate the track force of the new design. The paper closes with a design study at which the new design and the current design are compared to each other for different sized feet.